Comparative Analysis of the Training of Future Biology Teachers at the Universities of Ukraine and Poland - Biletska, Halyna; Mateyuk, Olesia (Pedagogical Discourse, 2020)
The features of preparation of future biology teachers at the universities of Ukraine and Poland are revealed in the article and the possibility of using the progressive ideas of the Polish experience in domestic higher education institutions is substantiated. As a result of studying educational programs and curricula, common features and differences in the professional training of biology teachers in Poland and Ukraine were identified. It has been found that the training of future biology teachers in Poland involves a fundamental biology training supplemented by a block of psychology and pedagogical disciplines. It has been found out that pedagogical training programs for future biology teachers at Polish universities are at least 25 ECTS credits and contain a significant list of academic disciplines that provide comprehensive and thorough training in pedagogical activities. It has been found that Polish universities offer ample opportunities for the mobility of educational participants. It is substantiated that the improvement of training of future biology teachers in Ukraine will be facilitated by the implementation of the following progressive ideas of the experience of Polish universities: deepening of general science training in biology, which will increase the employment opportunities for graduates; introduction of interdisciplinary training courses and integrated educational programs, which will broaden the range of subjects that the teacher can teach in general education institutions; reflection in the content of the disciplines of professional training of modern achievements of natural sciences and tendencies of their development, global problems of modernity and ways of their solution; introduction in preparation of future teachers of biology of psycho-pedagogical disciplines, the content of which reflects the current tendencies in education and the requirements of society for pedagogical staff; increasing the amount of practical training, conducting pedagogical practices throughout the semester, which will ensure the systematic practical training; an increase in the share of research work for the masters of higher education; expanding the international exchange of participants in the educational process.